The Linguistic Variability of the Kaunas District: The Basis for the Development of the "Tarmynas" Model - Bakšienė, Rima (Respectus Philologicus, 2021)
The article analyses the linguistic basis of the Tarmynas, the database Lithuanian local language variants. The development of the database model was based on the linguistic variability of the Kaunas district as an important zone for the development of Standard Lithuanian. Until now, the territory of the Kaunas district has not been systematically studied by dialectologists; therefore, the study is relevant in assessing the interaction between Standard language and local variants; the conclusions drawn are significant for prog-nostic models of the Lithuanian language. The analysis performed by the methods of geolinguistics research showed a significant horizontal and vertical variability of the Kaunas district. Based on the characteristics of the traditional dialects and their spread in the new dialectal structures, four linguistic areas of the Kaunas district were distinguished. Their main distinguishing features are the shortening of long vowels in unaccented inflexions and the hardening of the compounds le and lė. The influence of the local Polish dialects on the current linguistic variants was also identified. The possibilities of the explication of the dialectal phonetic features in the database are also briefly presented: transcriptions of acoustic recordings and a questionnaire about the frequency of usage of the dialectal features.